In (dependencia): secuencia de suspenso - Arancibia León, Bruno Caetano (2019)
(In)dependence was a silent minimalistic suspense sequence made in September, 2019 in Lima, Peru. It was directed by Caetano Arancibia and Rodrigo Farfán and stared Renato Medina (Alejandro) and Cheli Gonzalez (Cassandra). The main topics addressed in the sequence included toxic relationships, couple conflicts and the search for freedom. I was heavily influenced by films like “A Quiet Place” which heavily uses sound design to generate tension. The sequence told the story of Alejandro (28) who is isolated in an empty house, except for a few lamps he uses to light himself. Shortly after, Cassandra (23), his ex-partner mysteriously arrived at the house to recover Alejandro’s affection. However, he refused and took refuge in the light of his lamps. Cassandra, far from giving up, provoked and intimidated Alejandro by moving and turning off his lamps. Finally, both reconciled. The sequence was thought as two stories in one: the first in which a couple struggles to move away or reconcile and ends in a mutual understanding and the other as a personal journey where one learns to accept oneself and deal with loneliness.